Development and Validation of a Questionnaire for the Assessment of the Factors that Influence ADR Reporting by Pharmacists - Firdaus, Favian Rafif; Nita, Yunita; Setiawan, Catur Dian; Zairina, Elida (Borneo Journal of Pharmacy, 2024)
Drug safety is a significant concern in many countries, as side effects (AE) and adverse drug reactions (ADR) have caused many deaths worldwide. One of the reasons is the low contribution of pharmacists in spontaneously reporting AE/ADR. This study aims to develop a questionnaire to assess factors that correlate with spontaneous reporting by pharmacists. A questionnaire pilot was tested on 30 pharmacist respondents who worked in type C hospitals in Surabaya and Sidoarjo, Indonesia. Respondents' responses were then evaluated for face validity, construct validity, and reliability. The results showed that the face validity of the questionnaire was ideal. Then, the results of the construct validity of the knowledge section using point biserial correlation showed that two items were invalid because the r-value was smaller than the r-table (r = 0.361). Then, construct validity uses the factor analysis method for psychological, environmental, and practical variables by paying attention to the Kaiser-Mayer-Olkin Measure (KMO) value, which must be greater than 0.5, the significance of the Bartlett test, which must be less than 0.05 and the factor loading value which conditions must be greater than 0.5. As a result, most of the psychological, environmental, and practical variables show valid and reliable results. However, further consideration should be given to eliminating some items that do not meet the requirements. In conclusion, this validated questionnaire can be used to obtain additional information regarding factors influencing spontaneous reporting by pharmacists.